Long-term use of a combination of atorvastatin and ezetimibe in children with homozygous familial hypercholesterolemia - Dayal, Devi; Seetharaman, Keerthivasan; Bhunwal, Savita; Jain, Nimisha (International Journal of Contemporary Pediatrics, 2017)
Background: Homozygous familial hypercholesterolemia (HoFH) is an underdiagnosed and undertreated genetic disorder of lipoprotein metabolism associated with mortality during young age due to accelerated atherosclerosis. There is limited data on the efficacy of lipid lowering therapies in HoFH. Methods: Medical records of 3 children with HoFH who received a combination of atorvastatin and ezetimibe for a mean duration of 11.6±1.5 years were retrospectively analysed. Results: There was a significant decrease in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG) from the baseline levels (mean percent change in TC, LDL-C, TG and HDL-C of 58.5%, 56.2%, 67.5% and 29.7% respectively). Conclusions: We conclude that long-term use of a combination of atorvastatin and ezetimibe significantly lowers the plasma LDL-C concentrations in patients with HoFH without causing any significant adverse effects. Ours is the first study from India on long-term use of lipid modifying drug therapy in children with HoFH.